Huangshan population of Chinese Zacco platypus (Teleostei, Cyprinidae) harbors diverse matrilines and high genetic diversity - Zheng, Xin; Zhou, Tian-Qi; Wan, Tao; Perdices, Anabel; Yang, Jin-Quan; Tang, Xin-Sheng; Wang, Zheng-Ping; Huang, Li-Qun; Huang, Song; He, Shun-Ping (Dōngwùxué yánjiū, 2016)
Six main mitochondrial DNA (mtDNA) lineages have been described in minnow (Zacco platypus) samples obtained from northern, western and southern China. Perdices et al. (2004) predicted that further sampling of other tributaries might discover more lineages of this species. In this study, we collected 26 Zacco platypus individuals in the Huangshan area of eastern China and determined the cytochrome b (cytb) sequence variations. Combined with reported data in GenBank, we identified ten matrilines (Zacco A-J) in a total of 169 samples, with relatively high molecular divergence found among them. The Huangshan population had the greatest genetic variation among all sampled regions and hosted six of the ten matrilines. Our results highlight the significance of the Huangshan area for the conservation of Zacco platypus.